Magnetic resonance spectroscopic correlates of progression free and overall survival in “glioblastoma, IDH-wildtype, WHO grade-4” - Sacli-Bilmez, Banu; Danyeli, Ayça Erşen; Yakicier, M. Cengiz; Aras, Fuat Kaan; Pamir, M. Necmettin; Özduman, Koray; Dinçer, Alp; Ozturk-Isik, Esin (Frontiers in Neuroscience, 2023)
Background The 2021 World Health Organization (WHO) Central Nervous System (CNS) Tumor Classification has suggested that isocitrate dehydrogenase wildtype (IDH-wt) WHO grade-2/3 astrocytomas with molecular features of glioblastoma should be designated as “Glioblastoma, IDH-wildtype, WHO grade-4.” This study analyzed the metabolic correlates of progression free and overall survival in “Glioblastoma, IDH-wildtype, WHO grade-4” patients using short echo time single voxel 1H-MRS. Methods Fifty-seven adult patients with hemispheric glioma fulfilling the 2021 WHO CNS Tumor Classification criteria for “Glioblastoma, IDH-wildtype, WHO grade-4” at presurgery time point were included. All patients were IDH1/2-wt and TERTp-mut. 1H-MRS was performed on a 3 T MR scanner and post-processed using LCModel. A Mann–Whitney U test was used to assess the metabolic differences between gliomas with or without contrast enhancement and necrosis. Cox regression analysis was used to assess the effects of age, extent of resection, presence of contrast enhancement and necrosis, and metabolic intensities on progression-free survival (PFS) and overall survival (OS). Machine learning algorithms were employed to discern possible metabolic patterns attributable to higher PFS or OS. Results Contrast enhancement (p = 0.015), necrosis (p = 0.012); and higher levels of Glu/tCr (p = 0.007), GSH/tCr (p = 0.019), tCho/tCr (p = 0.032), and Glx/tCr (p = 0.010) were significantly associated with shorter PFS. Additionally, necrosis (p = 0.049), higher Glu/tCr (p = 0.039), and Glx/tCr (p = 0.047) were significantly associated with worse OS. Machine learning models differentiated the patients having longer than 12 months OS with 81.71% accuracy and the patients having longer than 6 months PFS with 77.41% accuracy. Conclusion Glx and GSH have been identified as important metabolic correlates of patient survival among “IDH-wt, TERT-mut diffuse gliomas” using single-voxel 1H-MRS on a clinical 3 T MRI scanner.